2022
DOI: 10.1002/anie.202207824
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Radical NHC Catalysis: Divergent Difunctionalization of Olefins through Intermolecular Hydrogen Atom Transfer

Abstract: Oxidative N-heterocyclic carbene (NHC) organocatalysis, typically leading to the formation of acyl azolium reactive intermediates, constitutes one of the most important activation strategies for the NHCcatalyzed chemical transformations. Here, we report an unprecedented oxidative radical NHC catalysis by using peroxyester as the external single-electron oxidant to realize divergent difunctionalization of olefins. The key to success of this chemistry is the catalytic generation of oxygen radicals that could tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 93 publications
0
18
0
Order By: Relevance
“…Steady-state fluorescence quenching experiments showed that the excited 4CzIPN* was quenched by potassium 2-ethoxy-2-oxoacetate 3 (section 3.2, ESI†). Based on the above experiments and previous reports, 11,13,15,17 we deduced the possible mechanism of the reaction (Scheme 5). The reaction involves a total of two catalytic cycles: the NHC catalytic and photocatalytic cycles, respectively.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Steady-state fluorescence quenching experiments showed that the excited 4CzIPN* was quenched by potassium 2-ethoxy-2-oxoacetate 3 (section 3.2, ESI†). Based on the above experiments and previous reports, 11,13,15,17 we deduced the possible mechanism of the reaction (Scheme 5). The reaction involves a total of two catalytic cycles: the NHC catalytic and photocatalytic cycles, respectively.…”
Section: Resultsmentioning
confidence: 71%
“…10 However, NHC-mediated 1,2-acylation of olefins was also reported. 11 In 2022, Larionov's group described the NHC-photocatalyzed tricomponent regioselective 1,2-diacylation of alkenes. 12 Very recently, our group reported that olefin diacylation products could also be obtained using benzoic acid as a reducing agent under the promotion of visible light.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to ionic-type (2-electron) mechanisms, thiazol-2-ylidenes have also recently become privileged organocatalysts for radical transformations of aldehydes. In these reactions, the Breslow-type enolates C – , which result from the condensation of aldehydes with NHCs in basic conditions, are able to undergo spontaneous single-electron transfer (SET) to challenging substrates ( E ox > −1.6 V vs SCE). In the absence of aldehydes, free NHCs are milder reducing reactants. For instance, imidazol-2-ylidenes perform stoichiometric reduction of the ferrocenium cation ( E = +0.38 V vs SCE) and the trityl cation ( E = +0.27 V vs SCE) .…”
mentioning
confidence: 99%
“…However, to the best of our knowledge, the reported protocols were mainly focused on the difunctionalization of activated alkenes (Scheme 1B). 6 The radical functionalization of unactivated alkenes via NHC catalysis has not been reported yet and remains challenging.…”
mentioning
confidence: 99%